Implementation of Food Ordering Application System Design in a Coffee Shop Using the Multilevel Feedback Queue Algorithm - Irwan Irwan; Muhammad Zen (SEAN Institute, 2023)
The exceptionally quick improvement of business urges each business person to make an alternate type of administration to draw in clients. Quick help is a fascination in itself for clients. In order to speed up food serving time and avoid a buildup of orders in the kitchen or chef, a queuing or scheduling system can be implemented. Staggered Criticism Line is a planning calculation for central processor planning for a PC working framework. The Staggered Criticism Line calculation permits cycles to move lines. A process will be moved to a lower queue if it consumes too much CPU, reducing the amount of CPU interaction time. In this exploration, an Android-based food requesting application was created by carrying out Staggered Criticism Line to make a line for food orders at the culinary specialist.